Malta : A Traveller's Anthology - Edited By Manley, Deborah (Luton Andrews UK, 2012)
Deborah Manley's selection of extracts reveals how generations of writers have viewed the landscapes of Malta and Gozo, the people of the islands, the splendours of Valletta and its famous harbour, and the celebrated festas, the village festivals that celebrate the island's Catholic identity. An introduction places these extracts in context, while the anthology also considers how Maltese writers have imagined and depicted their homeland.
Include Illustrations and Index
Keywords: Travelers' writings, English